(untitled) (Tydskrif vir Christelike Wetenskap | Journal for Christian Scholarship, 2015)
Our everyday experience is well acquainted with the reality of constancyand change. Persistence over time (continuity) is normally accompanied by an awareness of change (discontinuity). This article wants to highlightthe underlying ontological issues and distinctions required to gain a bet-ter understanding of the familiar term identity – in this case the identityof the Sabbath/Sunday. In the first part the distinction between continuityand discontinuity is investigated and described from an epistemological perspective. The second part deals with the way in which the distinction helps us to better understand the relation between the Sabbath and the Sunday. It is argued that this theme as dealt with in Scripture, entails an implicit awareness of the foundational relationship between constancy and change, thereby providing a philosophical perspective on the identity of this important institution of our Christian confession. The study is multidisciplinary. It includes hermeneutics, as well as a few remarks on rhetoric and Bible translation.